PENGARUH RETURN ON ASSET (ROA), DEBT TO EQUITY RATIO (DER) DAN EARNING PER SHARE (EPS) TERHADAP HARGA SAHAM PADA PERUSAHAAN SEKTOR BASIC MATERIALS YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2021–2025 - Thalia Putri Prihabsari; Almira Santi Samasta; Maria Safitri; Rudi Kurniawan (Politeknik Negeri Ambon, 2026)
Introduction: This study aims to examine the role of Return on Assets (ROA), Debt to Equity Ratio (DER), and Earnings per Share (EPS) in explaining stock price movements of Basic Materials companies listed on the Indonesia Stock Exchange over the 2021-2025 period. Stock prices reflect investors' responses to a company's financial performance, which is assessed based on information disclosed in annual financial reports. Previous studies have reported inconsistent findings regarding the effects of ROA, DER, and EPS on stock prices, indicating the need for further investigation.Methods: This study employed a quantitative research approach using secondary data obtained from annual financial statements and annual closing stock prices. The sample consisted of 75 companies selected through purposive sampling, resulting in 375 balanced panel observations. Panel data regression analysis was conducted using the Fixed Effect Model (FEM), which was selected based on the Chow and Hausman tests. To address heteroscedasticity, the estimation was performed using the Period Seemingly Unrelated Regression (SUR) method.Results: The results indicate that ROA and EPS have a positive and significant effect on stock prices, whereas DER has no significant effect. Simultaneously, ROA, DER, and EPS significantly influence stock prices. The model explains approximately 77% of the variation in the stock prices of Basic Materials companies.Conclusion and suggestion: This study demonstrates that profitability information carries greater weight than leverage in explaining investors' responses to Basic Materials companies. Strengthening asset productivity and maintaining sustainable earnings may therefore contribute to higher investor confidence and firm value. Expanding future analyses to include broader industry coverage, longer time horizons, and additional firm-specific and macroeconomic factors would improve the generalizability of the results. Keywords: ROA, DER, EPS, Stock Price, Basic Materials Sector